The cyclical character of fiscal policy in transition countries - Rilind Kabashi (National Bank of the Republic of Macedonia, 2016)
This study investigates the cyclical character of fiscal policy in transition countries in Central, Eastern and Southeastern Europe (CESEE) in the period from 1995 to 2011, using system GMM as the preferred estimation method for the underlying sample and model specification. The study finds discretionary policy in the CESEE EU Member States and in the Western Balkan countries to have been procyclical, thus aggravating economic fluctuations, whereas automatic stabilizers moved overall policy to an acyclical stance. In addition, the analysis indicates considerable differences in the cyclical character of fiscal policy between transition countries and the Western European EU Member States, where both overall fiscal policy and discretionary policy were acyclical. Finally, the study also offers several recommendations for policymakers, particularly in transition countries.
Keywords: H62; E32; C33; 330; fiscal policy; transition countries; European Union; system GMM